Higher education and the post-2015 agenda: a contribution from the human development approach. Issue 1 (2nd January 2016) - Boni, Alejandra; Lopez-Fogues, Aurora; Walker, Melanie
ABSTRACT: Sustainable Development Goals will guide the global development agenda for the coming years. Under this premise, this article explores the role which higher education (HE) has been assigned in contributing to sustainable human development, and concludes that the vision of HE offered is too narrow and unable to capture the essence and full meaning of sustainable human development. Moving away from problematic indicators and thresholds that understand HE as a producer of human capital, the article proposes placing the concept of human development at the centre of HE. Particularly, the article argues that its main elements (its normative approach, the idea of capability, functioning and agency) can provide a valuable and sound footing for a more transformative institution.